(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
In Japanese culture, using cloth as an environmentally friendly wrapper is known as Furoshiki. Furoshiki is useful for reducing the use of plastic bags, and it can be an alternative solution for environmentally friendly wrapping. The training was held in Jaya Village, Kuantan Singingi Regency. The training participants were 16 members of the Jaya Village PKK. The training is divided into two sessions: a presentation session on the benefits, types, patterns, and sizes of furoshiki cloth, while the second session is a workshop where participants practice variations of how to wrap goods with various furoshiki techniques by following the method demonstrated by the service members. This activity aroused the participants’ enthusiasm, and most participants could follow the method of wrapping step by step well. At the end of the activity, the team distributed a questionnaire to the participants to determine the achievement of the activity targets. The questionnaire found that the participants had high enthusiasm, a good understanding of furoshiki, the ability to practice various techniques, and high motivation to use furoshiki in everyday life. — Penggunaan kain sebagai pembungkus yang ramah lingkungan dalam budaya Jepang dikenal dengan Furoshiki. Furoshiki bermanfaat untuk mengurangi penggunaan tas plastik sehingga dapat menjadi solusi alternatif pembungkus yang ramah lingkungan. Pelatihan dilaksanakan di Desa Jaya Kabupaten Kuantan Singingi. Peserta pelatihan berjumlah 16 orang anggota PKK Desa Jaya. Pelatihan dibagi menjadi dua sesi; sesi pemaparan tentang manfaat, jenis, corak dan ukuran kain furoshiki sementara sesi kedua merupakan workshop dimana peserta mempraktikkan variasi cara membungkus barang dengan beragam teknik furoshiki dengan mengikuti cara yang telah didemonstrasikan anggota pengabdi. Kegiatan ini memunculkan antusiasme peserta dan mayoritas peserta dapat mengikuti cara membungkus tahap demi tahap dengan baik. Di akhir kegiatan, tim menyebarkan angket kepada peserta untuk mengetahui ketercapaian sasaran kegiatan. Dari angket tersebut diperoleh hasil bahwa peserta memiliki antusiasme tinggi, memiliki pemahaman baik terhadap pengetahuan mengenai furoshiki, memiliki kemampuan mempraktikkan berbagai teknik dan memiliki motivasi yang tinggi dalam memanfaatkan furoshiki dalam kehidupan sehari-hari.